Perfluoroalkyl substances (PFASs) and mercury in never-pregnant women of fertile age: association with fish consumption and unfavorable lipid profile. Issue 2 (4th November 2020) - Bjorke-Monsen, Anne-Lise; Varsi, Kristin; Averina, Maria; Brox, Jan; Huber, Sandra
Abstract : Objectives: To examine concentrations of perfluoroalkyl substances (PFASs) and lifestyle factors that may contribute to higher levels of pollutants in never-pregnant women of fertile age. Design: Observational cross-sectional study. Setting: Participants were recruited among employees and students at Haukeland University Hospital and the University of Bergen, Norway. Participants: Healthy, never-pregnant Norwegian women (n=158) of fertile age (18–39 years). Outcomes: Concentrations of 20 different PFASs, mercury (Hg), lead, cadmium, total, high-density lipoprotein and low-density lipoprotein (LDL) cholesterol, in addition to self-reported data on dietary intake. Results: Seven PFASs were detected in more than 95% of the women. Women aged 30–39 years had higher concentrations of sum PFAS compared with younger women. Serum PFASs were significantly intercorrelated (rho: 0.34–0.98, p<0.001) and six of them were significantly correlated to whole blood Hg (rho: 0.21–0.74, p<0.01). Fish consumption was the strongest predictor for most serum PFASs and for whole blood Hg. Fish consumption and serum perfluorooctanesulfonic acid (PFOS) concentrations were both positively associated with serum total and LDL cholesterol, established risk factors for cardiovascular disease. Conclusions: The majority of Norwegian never-pregnant women of fertile age had a mixture of seven different PFASs and Hg detected in their blood. PFAS concentrations were higher in older women and associated with fish intake. As the mean age of women at first birth is increasing, several factors require further consideration including diet, as this may influence the burden of PFAS to the next generation. Trial registration number: ClinicalTrials.gov ID: NCT03272022, Unique Protocol ID: 2011/2447, Regional Committee for Medical Research Ethics West (2011/2447), 12 January 2012.